Audiovisual strategies to foster listening comprehension process in students of the 7th grade at Beatriz Miranda de Cabal High School, 2017 - Ortíz, Hannia Massiel (UDELAS, 2017)
The project use the strategies for the development of listening comprehension arises from the need to increase the level of knowledge and understanding in the area of english in the institution, because due to the lack of documents and the lack of educational curriculum.